LINGUISTIC PROPERTIES OF LAWYERS’ SPEECH: A CASE STUDY - Hayrapetyan, Zara (Armenian Folia Anglistika, 2025)
The following article is focused on the integrative study of the court trial of Quaneesha Johnson who was accused of her boyfriend’s murder. The aim of the paper is to analyze the lawyers’ speeches and consider the linguistic and extra-linguistic means evident in them. The importance of the study lies within the outcome of the trial case, and, therefore, it is crucial to find the linguistic elements prevalent in those speeches. The lawyers’ speeches are of paramount importance and strictly conditioned by the persuasive and influential strategies and techniques to make an impact on the jury from the standpoint of the verdict to benefit the attorneys. This means that the lawyers are accepted to resort to rhetorical means to sound as convincing and persuasive as possible. Thus, our primary task is to study the speeches through the employment of the method of rhetorical analysis and reveal how artfully, strategically and effectively language is used by the lawyers in the courtroom to affect the court in the decision-making process. To find out the elements of persuasion it was also necessary to look into the semantic, and stylistic properties implemented in the speeches under investigation.